2015
DOI: 10.1021/acs.jmedchem.5b00921
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Substituted Naphthotriazolediones as Novel Tryptophan 2,3-Dioxygenase (TDO) Inhibitors through Structure-Based Virtual Screening

Abstract: A structure-based virtual screening strategy, comprising homology modeling, ligand-support binding site optimization, virtual screening, and structure clustering analysis, was developed and used to identify novel tryptophan 2,3-dioxygenase (TDO) inhibitors. Compound 1 (IC50 = 711 nM), selected by virtual screening, showed inhibitory activity toward TDO and was subjected to structural modifications and molecular docking studies. This resulted in the identification of a potent TDO selective inhibitor (11e, IC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 54 publications
(127 reference statements)
0
27
0
Order By: Relevance
“…Thus, TDO inhibition has emerged as a parallel immunomodulatory strategy to attack tumors (116121), the rationale for which has been reviewed recently by pioneers in this area (64, 115). An early bioactive inhibitor termed 68OC91 (116) has been used for mouse studies, but more potent and pharmacologically favorable compounds have been reported (117120). Deleting the TDO gene in mice ( Tdo2 ) causes L-tryptophan to accumulate and these mice show neurologic alterations, possibly due to serotonin elevation (122).…”
Section: On the Horizon: Tdo And Ido2 In Inflammatory Programming Andmentioning
confidence: 99%
“…Thus, TDO inhibition has emerged as a parallel immunomodulatory strategy to attack tumors (116121), the rationale for which has been reviewed recently by pioneers in this area (64, 115). An early bioactive inhibitor termed 68OC91 (116) has been used for mouse studies, but more potent and pharmacologically favorable compounds have been reported (117120). Deleting the TDO gene in mice ( Tdo2 ) causes L-tryptophan to accumulate and these mice show neurologic alterations, possibly due to serotonin elevation (122).…”
Section: On the Horizon: Tdo And Ido2 In Inflammatory Programming Andmentioning
confidence: 99%
“…Thus, there has been growing interest in small molecule inhibitors of TDO as a parallel immunomodulatory strategy to attack tumors (Abdel-Magid, 2017; Dolusic et al , 2011; Pantouris, Mowat, 2014; Pilotte et al , 2012; Salter et al , 1995; Wu et al , 2015), the rationale for which has been reviewed in detail recently by pioneers in this area (Platten et al, 2014; van Baren, Van den Eynde, 2015b). The initial bioactive lead structure developed in the 1990s termed 68OC91 (Salter et al, 1995) has been used for mouse studies, but compounds optimized for potency and more favorable pharmacological profiles have been reported (Dolusic et al, 2011; Pantouris, Mowat, 2014; Pilotte et al, 2012; Wu et al, 2015). Deletion of the TDO-encoding gene Tdo2 in the mouse causes higher concentrations of L-tryptophan to accumulate in blood, with some neurologic alternations perhaps attributable to a coordinate elevation in blood/brain levels of serotonin in these mice (Kanai et al , 2009).…”
Section: Tryptophan Dioxygenase (Tdo) In Inflammatory Programming: Immentioning
confidence: 99%
“…For example, a recent report describes Parkinsonism-associated symptoms with administration of indoximod (Floyd et al, 2016), an IDO inhibitor, although these symptoms have not been observed previously (Soliman et al, 2016), and it remains to be determined whether these symptoms are due to on-target toxicity. TDO-selective inhibitors have not progressed to the clinic to date, and reported inhibitors will require significant improvements in potency, selectivity, and ADME properties to progress into late preclinical studies (Pilotte et al, 2012;Wu et al, 2015). In summary, this class of agents has achieved a clinical proof-of-concept with the responses observed with epacadostat in combination with pembrolizumab.…”
Section: Tme-directed Approachesmentioning
confidence: 99%